Effects of carbon fiber reinforced polymer wrapping strength on behavior of steel hollow short column under concentric axial force - Kadhim, Ahmed Farhan (Al-Nahrain Journal for Engineering Sciences, 2026)
In this study, behavior of steel hollow short columns fabricated from steel square section under axial load is investigated with and without CFRP strengthening, five specimens of SHSC without strengthening are tested by applying concentric axial force; and the obtained results are compared with fifteen SHSC strengthened with CFRP wrapping with different five percentage from the total length of the specimens as follows (20%, 40%, 60%, 80%, and 100%) and each strengthening length consist from three different layers (one, two and three) layers. The curves of load-displacement are plotted for the specimens with maximum strength load. The results show that the most effective type of CFRP wrap strengthening is the full length of the specimens and especially with two and three layers. The increase in the load carrying capacity is 34.5% from 126.37 kN for SHSC-C to 170.02 kN for SHSC-100-3L, and the increase for ductility index is 23.6 % from 1.39 for SHSC-C to 1.72 for SHSC-100-2L. The pattern of failure for the specimens; non strengthened or strengthened with less than full length is local buckling, while the failure is CFRP rupture with local buckling for specimens strengthened with full length specimen.